Remarks by Bill Gates - Horvitz, Eric; Gates, William (CHI 2001 Conference on Human Factors in Computing Systems, Seattle, WA, 2001)
MR. GATES: Well, good morning, and welcome to Seattle. It was here in Seattle, about 30 years ago, that I first had a chance to use a computer. It was a teletype connected up to a GE timesharing system, and I can say that the user interface wasn't very good: very limited bandwidth, upper case only, but I did like the paper tape capabilities. What I wanted to do today is share some of the projects that Microsoft is involved in that we hope will create new frontiers for human/computer interfaces. I also thought I could take some of my favorite Microsoft error messages and get your feedback, this is one I just got recently. I think it's fair to say that Microsoft has done good things in computer/human interface, and also done its fair share of bad things as well. And so we look forward to participating in the conference, and seeing what new things we can do.